Literatur Review Pengembangan Instrumen Asesmen Pemahaman Konseptual Pada Pembelajaran Sains - Tanjung, Mardia Roza; Emilya, Wulanda Try; Festiyed, Festiyed; Mufit, Fatni (Universitas PGRI Semarang, 2022)
Conceptual understanding competence is something that every student must have. The concept understanding assessment instrument is something that cannot be separated in the achievement of students' conceptual understanding competence. Assessment is one of the measuring tools in the process of developing students' conceptual understanding. This research is literature review research on the development of conceptual understanding assessment instruments in science learning. There are 30 journals obtained from Google Scholar related to this research from 2014 to 2022.Â The results of this study show that first, based on the study ofÂ research objectives, it was found that the purpose of developing instruments was carried out at most, secondly, in terms of research design, the use of quantitative descriptive designs had the greatest frequency, Third, in terms of education level, most of this research was conducted at the SMA/MA/SMK level, fourth in terms of subjects that used concept understanding assessment instruments, most were obtained in physics subjects, and lastly, in terms of the type of instrument used, it was found that the rubric/ the most widely used concept understanding questionnaire. The lowest aspects of this research study can be recommended for other researchers for further research.Keywords: assessment, conceptual understanding, science